Students’ Perceptions of Using Digital Media in English Language Learning - Elisa, Lusi (Journal of Social Work and Science Education, 2023)
This study aims to determine the perceptions of students learning English using various digital media at the Islamic university level. This research uses a qualitative descriptive method, using observation and interviews. The research involved 10 respondents representing the Institute of Islamic Religion (IAI) Tulang Bawang, Lampung. Of the 10 respondents who answered the questionnaire, 87 percent stated why they prefer digital media over non-digital media. The reasons for these respondents are that digital media is more attractive, modern, and practical, in favor of students, and does not require a lot of paper. In addition, digital media can help students become autonomous and independent learners. This can also be used as a reference for developing independent curriculum implementation at KKNI level 6 in higher education.